Vocabulary improvement of elementary school children using puzzle technique - Salsa Dillah; Lollo Rosa Lubis; FriskaDani Hasibuan; Hotimayani Lubis (Jurnal ADAM : Jurnal Pengabdian Masyarakat, 2022)
Abstrack This community service focuses on learning to increase elementary school children's vocabulary using puzzle techniques. This service aims to increase the vocabulary in English for children at SD Negeri 200113 Tanobato. implementation method by learning while playing English puzzles and adding material orally and in writing. The service is carried out through three stages, namely the learning planning stage, the learning implementation stage and the learning evaluation stage. Vocabulary is important because learning vocabulary is the main capital for learning sentences and other skills in language. Mastering a lot of vocabulary will make it easier for them to read, write, listen and speak English. The success indicator in this learning is marked by the students' writing ability in learning English. At the implementation stage. The learning consists of three activities, namely opening activities, core activities and closing. This community service is carried out for three days. Some of the components that have been successfully achieved from this PKM include 1) the achievement of activity goals 2) the achievement of the material targets that have been planned. Abstrak Pengabdian kepada masyarakat ini fokus kepada pembelajaran peningkatan vocabularry anak sd menggunakan teknik puzzle. Pengabdian ini bertujuan untuk meningkatkan perbendaharaan kosakata dalam berbahasa Inggris anak anak di SD Negeri 200113 Tanobato. Metode pelaksanaan debgan cara belajar sambil bermain puzzle bahasa inggris serta menyampaikan materi secara lisan dan tulisan. pengabdian dilaksanakan melalui tiga tahapan, yaitu tahap perencanaan pembelajaran, tahap pelaksanaan pembelajaran dan tahap evaluasi pembelajaran. Vocabulary sangatlah penting karena mempelajari kosakata adalah modal utama untuk mempelajari penyusunan kalimat dan kemampuan lain dalam bahasa. Dengan menguasai banyak kosakata akan memudahkan mereka untuk membaca, menulis, mendengar dan berbicara bahasa Inggris. Indikator keberhasilan dalam pembelajaran ini ditandai dengan meningkatnya kemampuan menulis siswa dalam pembelajaran Bahasa Inggris. Pada tahap pelaksanaan. Pembelajaran terdiri dari tiga kegiatan yaitu kegiatan pembukaan, kegiatan inti dan kegiatan penutup.Pengabdian masyarakat ini dilaksanakan tiga hari. Beberapa komponen yang berhasil di capai dari PKM ini diantaranya 1) tercapainya tujuan kegiatan 2) tercapai target materi yang telah di rencanakan.